Pengaruh Penambahan Ubi Jalar Cilembu (Ipomoea batatas (L) Lam Cv. Cilembu) Terhadap Nilai Gizi Dan Sifat Sensoris Puding - Kurnia, Kholista Samsara; Kencana Putra, I Nengah; Sri Wiadnyani, Anak Agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 2 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i02.p08, 2023)
Pudding contains a fairly low nutritional value. Therefore, the addition of Cilembu sweet potatoes containing high nutritional values is needed to increase the nutritional value of pudding. This study aimed to find out the effect of the addition of Cilembu sweet potatoes on the nutritional value with sensory properties of pudding and determine the proper addition of Cilembu sweet potatoes in order to produce puddings with the best nutritional value with sensory properties. The experimental design used in this study is a Completely Randomized Design with the treatment of the addition of Cilembu sweet potatoes consisted of 5 levels: P1 (15%), P2 (30%), P3 (45%), P4 (60%), and P5 (75%). The treatment was repeated 3 times resulting in 15 experimental units. The data obtained were analyzed by Analysis of variance variety and if the treatment had a significant effect is continued with the Duncan Multiple Range Test (DMRT). The results showed that the treatment of Cilembu sweet potato addition had a real effect on water content, ash content, fat, protein, ?-carotene, color sensory, texture, taste, and overall reception. The addition of Cilembu sweet potatoes 45% produces the best characteristics which is water content 68.77%, ash content 0.48%, fat 19.59%, protein 0.98%, carbohydrate 10.15%, ?-carotene 1.20mg/100g, slightly yellow color, slightly chewy texture, sweet taste, and overall acceptance likes.